KEEFEKTIFAN MEDIA PEMBELAJARAN MONKESA BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN PENGETAHUAN SISWA PADA MATERI KEBERAGAMAN SUKU DAN BUDAYA KELAS V SDN BURENGAN 4 KOTA KEDIRI - Brisa Arimba Brigadeana; Muhamad Basori; Dhian Dwi Nur Wenda (Jurnal Manajemen Pendidikan, 2026)
The purpose of this research and development is to determine the effectiveness of MONKESA learning media based on local wisdom to improve students' knowledge on the material of ethnic and cultural diversity of grade V SDN Burengan 4 Kediri City. This research and development uses the ADDIE model which consists of the stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of this research are teachers and students of grade V SDN Burengan 4 Kediri City. The data analysis techniques used are qualitative and quantitative descriptive analysis. The results of this research show that the results of the limited scale effectiveness test show an average value of 84 and classical completeness of 100% with a very effective category. Then, the results of the broad scale effectiveness test show an average value of 86.94 which is rounded to 87 and classical completeness of 100% with a very effective category. The results of the study show that the MONKESA learning media based on local wisdom is very effective and can be implemented in learning the material on ethnic and cultural diversity in class V of SDN Burengan 4, Kediri City..